Geranylgeranylacetone decreases the production of hepatitis B virus‐related antigen by comprehensive downregulation of mRNA transcription activity. Issue 7 (12th January 2021) - Haraguchi, Masafumi; Miuma, Satoshi; Yamamoto, Kazuo; Nakao, Yasuhiko; Ichikawa, Tatsuki; Kanda, Yasuko; Sasaki, Ryu; Fukushima, Masanori; Akazawa, Yuko; Miyaaki, Hisamitsu; Nakao, Kazuhiko
Abstract: Background and Aim: Elimination of hepatitis B virus (HBV) is infrequently achieved with current therapies. Therefore, more effective anti‐HBV therapy is needed. We previously reported that geranylgeranylacetone (GGA) showed anti‐hepatitis C virus activity in human hepatoma cells. In this study, we examined the anti‐HBV activity of GGA. Methods: We used HepG2.2.15.7 cells, PXB cells infected with HBV, Huh7 cells transfected with linear HBV, and PLC/PRF/5 cells as HBV‐infected hepatocyte models. After GGA treatment, HBV‐related antigen was measured by chemiluminescent immunoassay. HBV‐related mRNA was examined by Northern blot. cccDNA and endoplasmic reticulum stress markers were measured by real‐time polymerase chain reaction. The activities of HBV promoters and enhancer regions were examined using luciferase vectors. Results: After GGA treatment, hepatitis B surface antigen and hepatitis B e antigen secretion was decreased in all HBV‐infected hepatocyte models. HBV‐related mRNA was also decreased by GGA treatment, although cccDNA levels were not affected. Additionally, the activity of HBV S1 and S2 promoter region and Enhancer 1/Enhancer 2/core promoter region was reduced by GGA treatment. The mRNA expression of the main transcription factors, hepatocyte nuclear factor 3 and 4 and CCAAT/enhancer binding protein, was also decreased. Further, the expression levels of endoplasmic reticulum stress markers were increased by GGA treatment, which reflected the change in HBV‐related antigen secretion. Conclusions: Geranylgeranylacetone treatment reduces HBV‐related protein levels by suppressing comprehensive downregulation of HBV promoter and enhancer activity, which might be caused by decreased hepatic transcription factor expression. GGA treatment may enhance anti‐HBV effects in combination with other therapies.